The role of the self-consistent equation in identifying the Andreev spectrum in a mesoscopic NS structure - Gogadze, G.A.; Dolya, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Adifferential self-consistent equation has been obtained for a dimensionless magnetic flux in a NS structure,which is responsible for the magnetic moment jumps in the system.